The Non-Receptor Protein Tyrosine Phosphatase PTPN6 Mediates a Positive Regulatory Approach From the Interferon Regulatory Factor to the JAK/STAT Pathway in Litopenaeus vannamei - Luo, Mengting; Xu, Xiaopeng; Liu, Xinxin; Shen, Wenjie; Yang, Linwei; Zhu, Zhiming; Weng, Shaoping; He, Jianguo; Zuo, Hongliang (Frontiers in Immunology, 2022)
SH2-domain-containing protein tyrosine phosphatases (PTPs), belonging to class Ⅰ PTP superfamily, are responsible for the dephosphorylation on the phosphorylated tyrosine residues in some proteins that are involved in multiple biological processes in eukaryotes. The Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway transducts signaling responding to interferons and initiates cellular antiviral responses. The activity of JAK/STAT pathway is generally orchestrated by the de-/phosphorylation of the tyrosine and serine residues of JAKs and STATs, in which the dephosphorylation processes are mainly controlled by PTPs. In the present study, a SH2-domian-contianing PTP, temporally named as LvPTPN6, was identified in Litopenaeus vannamei. LvPTPN6 sharing high similarity with PTPN6s from other organisms and was phylogenetically categorized into the clade of arthropods that differs from those of fishes and mammals. LvPTPN6 was constitutively expressed in all detected tissues, located mainly in the cytoplasm, and differentially induced in hemocyte and gill after the challenge of stimulants, indicating its complicated regulatory roles in shrimp immune responses. Intriguingly, expression of LvPTPN6 was regulated by interferon regulatory factor (IRF), which could directly binding the LvPTPN6 promoter. Surprisingly, unlike other PTPN6s, LvPTPN6 could promote the dimerization of STAT and facilitate its nuclear localization, which further elevated the expression of STAT-targeting immune effector genes and enhanced the antiviral immunity of shrimp. Therefore, this study suggests a PTPN6-mediated regulatory approach from IRF to JAK/STAT signaling pathway in shrimp, which provides new insights into the regulatory roles of PTPs in JAK/STAT signaling pathway and contributes to the further understanding of the mechanisms of antiviral immunity in invertebrates.